An intentional vocalization draws others’ attention: A playback experiment with wild chimpanzees - Crockford, Catherine; Wittig, Roman M.; Zuberbühler, Klaus (Animal cognition, 2015)
A vital step in the evolution of language is likely to have been when signalers explicitly intended to direct recipients’ attention to external objects with the use of referential signals. Although animal signals can direct the attention of others to external events, such as in monkey predator alarm calls, there is little evidence that this is the result of an intention to inform the recipient. Two recent studies, however, indicate that the production of chimpanzee quiet alarm calls, given to snakes, complies with some standard behavioral markers of intentional signaling, such as gaze alternation. But it is currently unknown whether the calls alone direct receivers’ attention to the threat. To address this, we carried out a playback experiment with free-ranging chimpanzees in Budongo Forest, Uganda, using a within-subjects design. From a hidden speaker, we broadcast either quiet alarm ‘hoos’ (‘alert hoos’) or acoustically distinguishable hoos produced while resting (‘rest hoos’) and found a significant increase in search behavior after ‘alert’ compared with ‘rest’ hoos, with subjects monitoring either the call provider or the area near the call provider. In sum, chimpanzee ‘alert hoos’ represent a plausible case of an intentionally produced animal vocalization (other studies) that refers recipients to signalers and/or to an external event (this study).